Ground reaction forces, rearfoot motion and wrist acceleration in nordic walking - Hagen, M.; Hennig, E. M.; Stieldorf, P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to analyze loading parameters in nordic walking (NW) compared to ordinary walking (W) with respect to upper and lower limb injury risks. 24 licensed NW-instructors, 12 male and 12 female (38±13 years, 175±9 cm, 78±14 kg, BMI 25±3 kg/m2), performed W and NW trials on a runway covered with artificial turf. Walking speed was controlled by two photo cells. By using an electrogoniometer and a Kistler platform, pronation and ground reaction forces were measured. Wrist acceleration was quantified by an uniaxial accelerometer attached to processus styloideus radii of the right forearm. Statistical evaluation was done by ANOVA and post hoc t-tests (p<0.05). Similar results were found for all three walking velocities chosen (5 km/h, 7km/h, 8 km/h). Except for the 2nd peak of the vertical ground reaction force, nordic walking results in higher loading rates and horizontal forces as well as higher pronation and pronation velocity values compared to ordinary walking. Wrist accelerations values up to 7 times gravitational acceleration were recorded in NW. The data clearly indicate that nordic walking can be recommended as low impact sport with relatively small loads to the lower extremities. However, the high wrist accelerations reveal that the upper extremities are exposed to considerable repetitive shocks, which may cause overuse injuries of wrist-, elbow, and shoulder joints. Thus, additional preventive exercises for the upper limb muscles are recommended as well as using shock absorbing walking poles.